Nanoscale characterization of aircraft soot: A high-resolution transmission electron microscopy, Raman spectroscopy, X-ray photoelectron and near-edge X-ray absorption spectroscopy study. (May 2016) - Parent, P.; Laffon, C.; Marhaba, I.; Ferry, D.; Regier, T.Z.; Ortega, I.K.; Chazallon, B.; Carpentier, Y.; Focsa, C.
Abstract: Particulate emissions from jet aircraft are a significant source of carbonaceous particles in the troposphere and lower stratosphere. Determining their physical structure and chemistry is relevant to assess their impact upon contrail formation, the radiative balance of the atmosphere, and human health. In this report, aircraft soot particles emitted by a recent turbofan engine, the PowerJet SaM146-1S17, fueled with Jet A-1, have been investigated with high-resolution transmission electron microscopy-in imaging, selected area electron diffraction mode, and energy dispersive X-ray spectroscopy -, Raman spectroscopy, X-ray photoelectron spectroscopy and near-edge X-ray absorption spectroscopy. This set of complementary techniques provides detailed structural and chemical information of the surface and the bulk of soot primary particles. Independently of the engine operating regimes, these particles are mainly composed of graphitic layers arranged in onion-like, turbostratic structures. They are poorly oxidized, with a slight enhancement of the oxidation rate at the very surface. The soot surface also presents a high concentration of unsaturated organic hydrocarbons and structural defects. These results allow a better description of aircraft soot at the atomic level, and may account for a better understanding of ice nucleation in aircraft contrails formation.